(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
A series of 4-(3-Chlorophenyl)-1-(substituted acetophenone) semicarbazones 3(a-j) was synthesized by starting with 3-chloroaniline which on reaction with sodium cyanate yielded 1-(3’-chlorophenyl) urea (1) followed by reaction with hydrazine hydrate in the presence of ethanol gave 4-(3’-chlorophenyl) semicarbazide (2). Compound (2) on condensation with substituted acetophenone gets converted in to final compounds 3(a-j). The purity of the newer compounds was checked by m.p. and TLC analysis. The structures of the newly synthesized compounds were characterized by FTIR, 1H NMR, EIMS-spectral data and elemental analysis. All the synthesized compounds were evaluated for their anticonvulsant activity by Maximal Electroshock (MES) method by using phenytoin as standard at a concentration of 30 mg/kg. The anticonvulsant effect of the newly synthesized compounds was assessed by absence or reduction of hind limb tonic extensor phase. Among the synthesized derivatives compounds 3e and 3j were found to be the most potent compounds in the series.